Utilização e significados atribuídos ao sinal de igual: um olhar para a produção escrita de alunos em provas de Cálculo Diferencial Integral I - Spielmann, Rosane (2019)
The equal sign is one of the symbols most used in mathematics classes and, therefore, received great attention from several researches that verified its inappropriate use by students throughout the Basic Education. In this sense, the intention of this research appeared in investigating the uses, omissions and meanings of the equal sign also in Higher Education. Thus, the work consisted in the analysis of the written production of students of Integral Differential Calculus (ICD), in which two evaluations were applied during the academic year 2015/2016 will be used in a first year group of Agricultural Engineering, of a state university of western Paraná. For this, we followed the question: from the written production of the students of the first year of graduation of an Agricultural Engineering course, what is possible to infer about the use of equal sign in their tests? With this, the objective was to understand the uses, omissions and meanings that the equal sign receives by Higher Education students in an evaluation situation. The posture assumed in the research is qualitative and based on the methodological approach of Content Analysis of Bardin. We take as theoretical guiding input the Analysis of Written Production as a Research Practice. Based on the analysis of these tests, we infer that the symbol is an item of secondary importance in the resolutions and we believe that this is a result of a school life where the students did not have contact with the different purposes and specificities that the symbol has